Visual evaluations of wind turbines: judgments of scenic beauty or of moral desirability? - Kirchhoff, Thomas; Ramisch, Kilian; Feucht, Tabea; Reif, Cedric; Suda, Michael (Landscape and urban planning, 2022)
To achieve a transition to renewable energy, large numbers of wind turbines have been built in Germany and in many other countries. Numerous surveys have been conducted to ascertain the subjectively perceived visual impact of wind turbines on the aesthetic quality of landscapes and the underlying factors of this impact. However, the extent to which moral judgments about wind turbines influence their aesthetic evaluation has until now never been studied. To address this issue, we investigated the influence of implicit moral associations and judgments of different large-scale mast-like structures—namely wind turbines, incinerator plant chimneys and high-frequency communication towers—on statements about the impact of these structures on the visual quality of landscapes. We found that mast-like structures which barely differ in visual terms are nevertheless judged to impair the visual quality of landscapes to very different degrees. These correlations held true for both supporters and opponents of wind energy. Furthermore, we looked for correlations between the evaluation of wind turbines and general attitudes towards them, and ascertained that supporters of wind energy tended to rate landscapes with wind turbines substantially higher than non-supporters. A possible explanation for this is the structures’ significantly different moral associations. Our findings support the hypothesis that statements about the visual impact of mast-like structures in landscapes are strongly influenced by (implicit) moral judgments on these structures that are driven by their moral associations. Thus, to a considerable extent, such statements reflect not judgments on scenic beauty but moral judgments. These findings have substantial implications not only for the assessment of the impact of wind turbines on the landscapes’ scenic qualities but for the interpretation of visual landscape quality assessments in general. We propose a methodological approach to overcome these problems.
Gesehen am 20.07.2022